The Effect of Teachers’ Classroom Test Writing Practices on Students’ Perceived Ratings of Continuous Assessment and College Cumulative Grade Point Averages: The Case of Ethiopian Civil Service and Adama Science and Technology Universities - Sherkabu, Desalegn (African Journal of Leadership and Development, 2019)
This paper aims at investigating classroom test Item Writing Practices and challenges of evaluation in the Ethiopian Civil Service University (ECSU) and Adama Science and Technology University (ASTU) with their 370 and 172 sampled university students and instructors respectively. A concurrent quantitative qualitative (QUAN-QUAL) mixed descriptive design was employed. While the universities and faculties and/or departments were chosen by using purposive bases of relative similitude, the sixteen academic leaders and the 13 exam booklets were sampled on accessibility basis. Thus, the study was based on purposive sampling. Data were collected using two sets of questionnaire for the former two sets of respondents, and FGD and interviewees were arranged with the other two groups of respondents. In the questionnaire, the researcher designed a five point Likert scale with 49 items under 11 categories for student respondents, and a five point Likert scale with 61 items under 6 major categories for instructor respondents. Sample examination booklets were closely studied qualitatively. The quantitative data were analyzed using multiple linear regression technique. The study depicted a moderately high rate of standard- about 65.2-80% on the five point scale questionnaire filled in by students. It also revealed (r=0.47), a moderately positive relationship pointing out that a unit of change in college entrance examination (ESLCE) resulted in forty-seven units of change in college CGPA which is direct substantiation of the trend to be in its normal course. Students rated ethical standards as low which verifies the qualitative evidence to the sagging quality of the assessment, contrary to the quantitative data. Accordingly, the assessment and evaluation practices demonstrated both positive achievements and deficiencies. Finally, recommendations were made including a call for a firm follow-up of the process.